Bacterial Desulphurization of Coal from Jaworzno Mine (ABSTRACT PAGE) - Peter Fecko; Pavla Ovcarí; Barbara Tora; Hong Nguen Vu (International Mineral Processing Congress, 2003)
"The goal of the work was verification of bacterial leaching on the samples of black coal. From the results obtained it was clear that the coal is very well leached by Thiobacillus ferrooxidans and this technology can be used for coal desulphurization. A leaching time of one month is required, to remove 65% of total sulphur and 85% of pyritic sulphur.Microscopic evaluation of samples from Jaworzno showed, that it should be classed as a coal with low coalification, probably from black coal hemiphase. Macerals of the liptinite group were well distinguishable; they were of a dark brown colour. Evidence of coal mass oxidation was apparent on the fresh sample; in the test samples (during bacterial leaching) small grains were oxidised."